The factors that influence the buying selection of apartment in Johor Bahru / Nurul Farhana Rahmat - Rahmat, Nurul Farhana (2011)
By recognizing the fact that the property market becomes competitive, a full understanding of house buyers’ needs, preferences, attitudes and buying behavior is important for the market leading developers to always survive in market. Hence, a research regarding on buying selection is necessary to overcome the problem by focusing on customer decision making process. The objective of this research is to identify the most important factors that influence the buying selection of apartments in Johor Bahru and also wants to examine if demographic characteristics (gender, age levels, and race) have a relationship on the buying selection of an apartment. A sample consists of 100 persons who has an apartment in Johor Bahru was chosen to be a respondent. The respondent was highlighted that facilities is the most important factors to them to purchase an apartment. Followed by location, neighborhood, comfortable and Feng Shui factor. The findings also revealed that gender, age levels and races has no relationship on the buying selection an apartment.